KAJIAN FENOMENOLOGI TENTANG PENGARUH PERBAIKAN LAPANGAN TERHADAP MOTIVASI BELAJAR SISWA DI MI TERPADU MUTIARA ASSYIFA KOTA BENGKULU - Febriani, Hanura; anggraini, Juwita; sri marisa, Rika; Ulandari, Rahma (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
Learning motivation plays an important role in educational success, with physical facilities such as sports fields influencing students' motivation to participate in learning. This study aims to examine the effect of sports field improvements on students' learning motivation at MI Terpadu Mutiara Assyifa. A phenomenological approach was used to explore students' subjective experiences related to field improvements, which involved interviews, observations and students' reflective journals. The results showed that the field improvements, which included a more level surface and adequate supporting facilities, increased students' comfort and sense of security. These improvements not only affected students' motivation in sports activities, but also increased their motivation in academic learning. Students felt more enthusiastic to participate in learning after the field improvements, and they gave positive meaning to the changes. This study confirms that good school facilities have a significant impact on students' intrinsic and extrinsic learning motivation and can support the achievement of holistic education goals.